2013
DOI: 10.1097/sap.0b013e31828986c9
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Review of the Treatment Patterns of Traumatic Thumb Amputations

Abstract: Traumatic thumb amputations are a common problem with significant associated cost to patients, hospitals, and society.The purpose of this study was to review practice patterns for traumatic thumb amputations using the National Trauma Data Bank. By using a large nationwide database, we hoped to better understand the epidemiology and predictors of attempts and successful replantation.The design was a retrospective review of the National Trauma Data Bank between the years 2007 and 2010, investigating patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
5
31
1
Order By: Relevance
“…We recognise that our reported survival rates for digital replantation still seem to be significantly lower than the published figures, 71-93 % [1,3,12,13]. Although clean cut guillotine type mechanisms are regarded as the most favourable for replantation [9], this was a relatively rare occurrence in our study cohort with only five digits being injured in this way.…”
Section: Discussioncontrasting
confidence: 79%
“…We recognise that our reported survival rates for digital replantation still seem to be significantly lower than the published figures, 71-93 % [1,3,12,13]. Although clean cut guillotine type mechanisms are regarded as the most favourable for replantation [9], this was a relatively rare occurrence in our study cohort with only five digits being injured in this way.…”
Section: Discussioncontrasting
confidence: 79%
“…To obtain the failure rate of digital replantation from this population-based study, we followed Shale et al's study 8 and assumed that patients who underwent replantation and amputation during single hospitalization were replantation failures.…”
Section: Failure Of Replantationmentioning
confidence: 99%
“…Shale et al 17 described 3341 patients with thumb amputations treated at 474 hospitals. Nonteaching hospitals treated 37% (1238/3341) of patients and attempted replantations for 10% (123/1238) of those patients with an 81% success rate.…”
Section: Resultsmentioning
confidence: 99%
“…Further nationally representative studies of hand trauma care in the U.S. are required. Third, except in a few studies, 17 severity of hand injuries were not reported, which made comparisons of the findings difficult. Despite these limitations, this study provides a comprehensive view of challenges facing the hand trauma care in the U.S.…”
Section: Discussionmentioning
confidence: 99%